Pembacaan Non-Homofobik Terhadap Ayat-ayat Sejarah Homoseksualitas Dalam Alquran: Menuju Penafsiran Sensitif-Seksualitas - Muhammad Dluha Lutfillah (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2018)
The Muslim understanding of the Qur'anic verses about the history of homosexuality particularly the phrase ma sabaqakum biha min ahad min al-'alamin for centuries reads that no man before your people the prophets Lut’s people, more than 20th BC who ever took action fakhisha ' which is then interpreted by the so-called' neo-orthodox 'as homosexuality. This understanding is in the contrary with the results result of an Egyptologist Greg Reeder saying that the first possible homosexual couple were Niankhkhnum and Khnumhotep, two manicurists at the age of the Fifth Dynasty of the Kingdom of Ancient Egypt (more than 25th BC). The contradiction then inspects a man on the question of “Whether Qur'an incorrectly cite the history?” Suspicion is suspended by al-Razi which provides a more accommodative alternative to the Reeder study, which is 'beyond what you do in it' which gives the possibility of a group of people who did homosexuality in the past 20 BC.